2015
DOI: 10.1038/ncomms7281
|View full text |Cite
|
Sign up to set email alerts
|

The polymeric mucin Muc5ac is required for allergic airway hyperreactivity

Abstract: In asthma, airflow obstruction is thought to result primarily from inflammation-triggered airway smooth muscle (ASM) contraction. However, anti-inflammatory and smooth muscle-relaxing treatments are often temporary or ineffective. Overproduction of the mucin MUC5AC is an additional disease feature that, while strongly associated pathologically, is poorly understood functionally. Here we show that Muc5ac is a central effector of allergic inflammation that is required for airway hyperreactivity (AHR) to methacho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
227
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 248 publications
(250 citation statements)
references
References 71 publications
19
227
0
Order By: Relevance
“…We conducted the PAS staining for mucin after BAL and after methacholine challenge. In this context, it was previously demonstrated, using quantitative morphometry, that there is an acute decrease in mucin content in the epithelium that represents the release of mucin from the epithelium (38). We found that there was a significant decrease in mucin staining relative to the epithelial area in the Pla2r1 2/2 mice relative to WT controls (P = 0.01, Figure 6A).…”
Section: Pla2r1supporting
confidence: 54%
“…We conducted the PAS staining for mucin after BAL and after methacholine challenge. In this context, it was previously demonstrated, using quantitative morphometry, that there is an acute decrease in mucin content in the epithelium that represents the release of mucin from the epithelium (38). We found that there was a significant decrease in mucin staining relative to the epithelial area in the Pla2r1 2/2 mice relative to WT controls (P = 0.01, Figure 6A).…”
Section: Pla2r1supporting
confidence: 54%
“…Goblet cell hyperplasia and mucus hypersecretion are important features in the conducting airways during allergic asthma, and extensive mucus plugging is associated with fatal asthma episodes (41). Animal models of allergic asthma support the critical role of the mucin gene Muc5ac in the development of mucus obstruction and airway hyperreactivity (42). The process of mucus hypersecretion during allergic asthma involves a complex multistep process, including mucin gene induction, mucus packaging in storage granules, mucus secretion, and changes in extracellular mucus viscosity.…”
Section: Discussionmentioning
confidence: 99%
“…Such a scenario could explain attenuation of AHR in Glrx1 2/2 mice, despite the apparent similar extent of overall mucus metaplasia. Previous studies have suggested that inflammation-triggered airway smooth muscle contraction alone is not sufficient for airway hyperreactivity to methacholine, and that noncontractile factors, such as mucus, are essential for AHR (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%